A STUDY ON SUITABILITY OF UNIVERSAL SERVICE OBLIGATION WI-FI HOTSPOTS SCHEME FOR REDUCING DIGITAL DIVIDE - Chandra Sekhar, Susarla; Santhisree, Dr. V.N. (The journal of contemporary issues in business and government, 2022)
There is a paradigm shift in the Telecom services world over and no exemption in India too. The telecom sector had been transformed from traditional landline services to broadband, WiFi and subsequently to mobile internet facilities. Overall the focus had been shifted from basic services to the data services. In order to understand this there is a need to study the requirement of Internet and data services in India and provision of these facilities to rural and remote areas on subsidy through Universal Service scheme by Government of India. This paper first aimed at showing the trends in the telecom and internet services in India, secondly to give a brief picture about various Wi-Fi Flotspot schemes through Universal Service Obligation (USO) fund. Finally the gaps between rural and urban areas have been explained and also the future requirements were forecasted.